The views of the young generation of a city as a common good - Agnieszka Sobol (Economic and Environmental Studies (E&ES), 2016)
Alongside increasing urbanization, the city has become a particularly important subject of studies. Cities bear the brunt of the most intense indicators of civilization processes and social change. Simultaneously, the influence of the civilizing processes and the deepening of globalisation have both acted to reorient the approach towards local development. The aspiration of sustainable development requires us to resolve common problems and to recognize new perspectives. The trends of urban development determine the quality of life of an increasing number of city dwellers. Evolution of the paths of local development should be a response to the new needs of cities and their residents. Increasingly more attention is paid to such categories as the commons, social capital and the quality of life. Understanding the concept of a common good in relation to urban development appears to be a singularly topical issue. The aim of the article is to give an overview of the perception of the commons in the modern urban societies with an accent on the young generation. Do present-day young residents perceive the city as a common good? The article tries to give an answer for the above question based on theoretical review, worldwide surveys and an empirical studies conducted by the author among high-school students. It is a voice in an important debate on the commons showing the role of an education and the young in transformation of cities towards sustainability. Although the paper provides some insights for researchers and practitioners, some limitations of the findings should be mentioned. During the study, the judgmental sampling method was adopted, thus, the results cannot be generalized to the general youth population. Also the complex subject is not exhaustively described.
Keywords: I25; P48; Q01; 330; common good; sustainable development; young generation; city